THE INFLUENCE OF LIFESTYLE ON FERTILITY (Vietnam Journal of Community Medicine, 2022)
Infertility tends to increase, there have been numerous studies on the causes of infertility suchas age, gynecological diseases, and genetic causes... however, the influence of lifestyle onfertility is still little known. The purpose of this report is to provide an overview of severallifestyle behaviors that affect fertility. Methods used are reviewing studies on a number oflifestyle behaviors that affect reproductive capability. Conclusion & recommendations: Inplanning for pregnancy, couples should quit smoking, try to maintain a BMI of 18.5 - 25 kg/m2, should exercise, but not more than 5 hours/week; Women who are planning to becomepregnant, are pregnant should avoid alcoholic beverages, because the level of safe alcoholconsumption for the fetus has not been determined, limit caffeine consumption.
Keywords: Infertility, tobacco, BMI, alcohol, coffee, exercise/sports, psychology.